Professional guide to signs & symptoms (Springhouse Corp., 2001)
Guide to more than 550 signs and symptoms with nursing implications in a concise format. For nurses. More than 500 illustrations, flowcharts, tables, and reproducible patient teaching aids are also included. A-to-Z organization for quick access.